Афера в каменных джунглях: [повесть] / Марина Серова - Серова Марина Сергеевна (Русский бестселлер, 2019)
Экземпляры: ЦГДБ (20210707) / Инвентарный номер: 94482 / Цена: 174.90 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: С 32 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус2)6-44